Employability of Female Graduates in a Quasi-Military Maritime Higher Education Institution: Towards Gender Equality in the Maritime Industry - Taberdo, Ana Liza; Paraggua, Victoria; Alvarez, Myrna; Acuavera, Ronalyn; Pasa, Geraldine (JPAIR Multidisciplinary Research, 2021)
The Commission on Higher Education (CHED) underscores the value of conducting graduate employability studies in higher education institutions. On the other hand, the Philippine Commission on Women (PCW) battles for the empowerment of women, notably those who are seafarers assigned to work-aboard inter-ocean ships. The study traces the employment, career path, and relevance of the curriculum and competencies learned in the academy and gender issues experienced by the 26 alumnae of the Philippine Merchant Marine Academy (PMMA) who graduated in 2013-2018. The quantitative-descriptive research design was utilized. A researcher-made questionnaire both via Google form and print-out was the main data gathering instrument. Data were analyzed using frequency, percentage, mean and Likert scale. Data shows that the female graduates are single, with an OIC license, able to land a job 1-6 months after graduation and mostly working in either an international ocean-going vessel or serving at the Philippine Coast Guard. They also perceive that they have acquired all competencies in PMMA to a great extent which become handy in their respective jobs. Further, they strongly agree that they have acquired work-related values from PMMA and that the curricula at the Academy are relevant. Unfortunately, most of them have experienced gender inequality. The findings imply that even if the alumnae were skilled and had the necessary competencies, gender inequality is still prevalent in the male-dominated industry. The incidence of inequality was mostly experienced in the assignment of tasks and finding a job.